2020
DOI: 10.1111/jorc.12314
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy in Kidney Disease: Associations with Quality of Life and Adherence

Abstract: SUMMARY Background Health literacy (HL) is a multidimensional concept with significance for self‐management and health outcomes in patients with chronic kidney disease (CKD); however, research with a multidimensional perspective on HL is scarce. Objectives This study aimed to explore the relationship between multidimensional HL, quality of life (QoL) and adherence to long‐term therapy in CKD patients. Design A descriptive single‐centre cross‐sectional study. Participants Patients with CKD in stages 3–5 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 59 publications
(55 reference statements)
3
28
0
1
Order By: Relevance
“…We found that patients in the moderate HL group were more likely to be non-adherent with diet, but we did not confirm it in patients in the low HL group. This is in line with the research findings of Stømer et al [49] who focused on HL of CKD patients and its association with adherence to lifestyle recommendations and brought similar findings to ours, that patients with moderate HL reported worse adherence than patients with higher HL, but they did not find low HL group to be significantly different than moderate or high HL group. As end stage renal disease (ESRD) is a result of long-term health problems and occurred frequently in the elderly, patients with low HL may already depend their diet adherence on caregivers (spouse, family members), or simplify their diet regime to avoid non-adherence.…”
Section: Discussionsupporting
confidence: 93%
“…We found that patients in the moderate HL group were more likely to be non-adherent with diet, but we did not confirm it in patients in the low HL group. This is in line with the research findings of Stømer et al [49] who focused on HL of CKD patients and its association with adherence to lifestyle recommendations and brought similar findings to ours, that patients with moderate HL reported worse adherence than patients with higher HL, but they did not find low HL group to be significantly different than moderate or high HL group. As end stage renal disease (ESRD) is a result of long-term health problems and occurred frequently in the elderly, patients with low HL may already depend their diet adherence on caregivers (spouse, family members), or simplify their diet regime to avoid non-adherence.…”
Section: Discussionsupporting
confidence: 93%
“…We found that patients with lower HL suffer from worse HRQoL than patients with moderate or higher HL. This confirms the findings of Dodson et al and Stømer et al [18,22], although they used a different measurement tools for assessing HRQoL and assessed less domains of HRQoL. The current study provided a better understanding of the impact of HL on different domains.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with limited HL may fail to understand and apply health information for appropriate self-care activities, and limited HL may highly affect dialyzed patients, who have to adhere to strict recommendations regarding diet, medications and dialysis and must effectively cooperate with healthcare providers. These challenges may in turn negatively affect the quality of their physical health, mental health and social life [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study investigating these associations. In the literature, higher HL scores were found to be associated with better adherence to therapies among people with chronic diseases [73][74][75][76]. Receiving COVID-19-related information online during the pandemic could be beneficial for various preventive behaviors [77].…”
Section: Principal Findingsmentioning
confidence: 99%